Perlindungan Hukum Terhadap Pekerja Lanjut Usia Berdasarkan Hukum Ketenagakerjaan (Kasus Pengemis Online dalam Konten Mandi Lumpur di Tiktok) - Muhamad Farudin (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study examines the increasing number of elderly individuals working in the informal sector and the exploitation risks they face, particularly through social media. According to data from BPS, there has been a rise in active elderly workers, with most employed in the informal sector. Indonesia's Labor Law does not provide specific protections for elderly workers, making them vulnerable to exploitative actions, such as the "online begging" phenomenon on TikTok, which leverages viewers' empathy. This study employs a normative juridical approach to identify legal gaps in labor regulations concerning elderly workers and analyze the impact of inadequate protection. The results indicate that elderly workers on digital platforms require stricter regulations regarding work conditions and rights protection. This study recommends more inclusive policies to ensure the welfare of elderly workers, particularly those in the informal and digital sectors, and emphasizes the need for transparent employment agreements and strict regulation on social media platforms.